Symposium 11: The Learner's Experience of a Networked Learning Knowledge Community Design - Hodgson, Vivien; Watland, Philip (Proceedings of the International Conference on Networked Learning, 2004)
The purpose of the study that will be reported in this paper is to investigate the learning experiences in a Masters degree program whose design is based on a ‘knowledge community’ pedagogical perspective. The MA is supported by a network learning environment that includes several different areas and discussion forums intended to encourage ‘dialogical learning’. The study aims to compare and contrast the learners’ experiences with the pedagogical intentions of the program design. The context for the study is a Lancaster University’s MA in Management Learning and Leadership (MAMLL) programme. This is a two-year programme directed towards people in, or entering, leadership and/or management development roles. The programme attracts a diverse range of participants from public, private and voluntary organisations. A principle concept of the program is that learners help create the learning environment, a knowledge community, by building their own representations of management learning using the capabilities of on-line technologies to enable dialogical learning (Hodgson and Zenios, 2003). In the study, it is the learner’s experience of the MAMLL networked learning environment that is of interest.